Penerapan ISAK 335 pada Organisasi Yayasan di Indonesia: Evaluasi Kesiapan Institusional, Analisis Empiris, dan Prospek Akuntabilitas Nonlaba - Mahyuni; Basyirah Ainun; Lusiana Handayani; M. Yasir Fahmi (P3M Politeknik Negeri Banjarmasin, 2026)
Non-profit organizations, particularly foundations (yayasan) in Indonesia, play an essential role in the social and religious sectors. Unlike commercial entities, their operational sustainability depends heavily on public trust and donor funding, necessitating a highly transparent financial reporting framework. The transition from PSAK 45 to ISAK 335 fundamentally shifted the paradigm of non-profit accounting by requiring strict segregation of net assets based on donor restrictions. This study evaluates the empirical readiness of foundations to implement ISAK 335. Findings reveal significant compliance gaps driven by reliance on simple cash-basis accounting, lack of competent human resources, financial constraints, and inadequate socialization. Post-Implementation Review (PIR) by IAI in 2025 further highlights complexities in restricted grants and endowment funds. To bridge these gaps, this article proposes strategic solutions, including the restructuring of the Chart of Accounts (CoA), strict Standard Operating Procedures (SOP) for donations, digital transformation via specialized accounting software, and intensive mentorship from professional bodies and academia.